Extracorporeal and Conventional Cardiopulmonary Resuscitation and Low‐Flow Duration: Insights From a Nationwide Hospital‐Based Registry Study in Japan (JAAM‐OHCA Registry) - Tasuku Matsuyama; Bon Ohta; Sho Komukai; Sheldon Cheskes; Steve Lin; Rohit Mohindra; Ian Drennan; Johannes von Vopelius‐Feldt; Tetsuhisa Kitamura (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background The optimal low‐flow duration (LFD) for extracorporeal cardiopulmonary resuscitation (ECPR) and conventional cardiopulmonary resuscitation (CCPR) remains unclear. We evaluated the impact of LFD on neurological outcomes based on initial cardiac rhythms and compared trends between ECPR and CCPR. Methods This secondary analysis used data from a nationwide, prospective study of adult (≥18 years) nontraumatic patients with out‐of‐hospital cardiac arrest receiving cardiopulmonary resuscitation upon hospital arrival (June 2014–December 2019). LFD was defined as time from professional cardiopulmonary resuscitation initiation to ECPR initiation or return of spontaneous circulation/termination of resuscitation in CCPR. The primary outcome was 1‐month survival with favorable neurological status (Cerebral Performance Category scale 1 or 2). Patients were stratified into 4 groups based on first documented cardiac rhythm (pre‐ or in‐hospital). Results Among 42 365 patients (1355 ECPR, 36 991 CCPR), longer LFD was associated with poorer neurological outcomes in patients with initial shockable rhythms, regardless of ECPR or CCPR use. The highest favorable outcome rates were observed in the Shockable–Shockable groups (ECPR: 16.0%; CCPR: 16.9%), with a clear decline in outcomes as LFD increased (both P for trend <0.001). In contrast, this trend was absent in ECPR‐treated patients with initial nonshockable rhythms, who had consistently poor outcomes. Conclusions Longer LFD is associated with worse outcomes in patients with initial shockable rhythms. This association was not observed in nonshockable cases, although their prognosis was generally poor. Defining rhythm‐specific LFD thresholds may guide ECPR use and improve outcomes.